SIKAP PEKABARAN INJIL TERHADAP AGAMA SUKU DAN IMPLEMENTASI-NYA DALAM PENDIDIKAN AGAMA KRISTEN - Ridwan Rudiyanto Kajah Kore; Rita; Marisa Levinda Atamou; Marla Kristin Manu; Jefan Dreanzy Marjunov Kadjakoro; Maurelia H.W Ratuwalu (JOURNAL OF COMMUNITY DEDICATION, 2025)
The proclamation of the Gospel within a pluralistic society requires evangelists to possess a wise and compassionate attitude toward indigenous religions. In the context of Indonesia, which is rich in cultural and religious diversity, the interaction between evangelists and adherents of indigenous faiths demands deep understanding to avoid cultural clashes or feelings of threat among those being served. This study aims to examine the attitudes that evangelists should embody toward indigenous religions and how the positive values within them can be appropriately integrated into Christian Religious Education (CRE). The research method used is a literature review combined with theological reflection, emphasizing the principles of Gospel contextualization, intercultural dialogue, and respect for the noble values present in indigenous religions. The findings reveal that an effective evangelist’s attitude must include humility, openness, respect for local culture, and a willingness to build healthy dialogue. In its implementation in CRE, this can be realized through the development of teaching materials that honor local wisdom, encourage students to understand cultural and religious diversity, and instill the universal love of Christ. Thus, Christian Religious Education not only serves as a means of teaching faith but also shapes students’ character to be tolerant, open, and ready to bear witness in a multicultural society. Such awareness is expected to minimize conflict, build bridges of understanding, and strengthen the witness of the Gospel within a multicultural context.